(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To analyze the outcomes of dome osteotomy for correction of cubitus varus deformity. Methods: We managed 14 children of cubitus varus between 7-11 years age, with dome osteotomy correction. Of these patients 9 were boys and 5 were girls. This retrospective study was carried out from Jan 2011 to June 2012. Mean pre-operative angles were 7 degrees varus (5-14 degrees) and post-operative correction was aimed to get an angle of 9 degrees valgus. All patients were followed up for 01 year. The main criterion against which the outcomes were assessed included the range of motion of their elbow joint, degree of correction of carrying angle and lateral condylar prominence index. Results: In light of the assessment criterion the outcome was found to be excellent in 11 cases and good in 03 patients. Clinical and radiological bone union was achieved in all cases at 10 weeks. Few complications were also seen which included painful scar formation, ulnar neurapraxia and pin tract infection. The mean lateral prominence index did not increase postoperatively Conclusion: Dome osteotomy was found to be an exceptional technique to treat cubitus varus with no resultant iatrogenic deformity of lateral condylar prominence. Key Words: Outcome, Cubitus Varus, Dome Osteotomy.